2015
DOI: 10.1111/1095-9270.12109
|View full text |Cite
|
Sign up to set email alerts
|

The Port-Vendres 4 Shipwreck Cargo: evidence of the Roman wine trade in the western Mediterranean

Abstract: The Port-Vendres 4 shipwreck is evidence of coastal export trade between Hispania Citerior and Narbonne in 40/30 BC. The cargo is made up of a particular assemblage of Roman wine amphoras (Pascual 1, Dressel 1B and Lamboglia 2) destined for Gallic markets. Archaeological and archaeometric analyses conducted on a selection of the amphoras allowed the provenance of the cargo to be identified as Hispania Citerior and the central-southern Tyrrhenian coast of Italy. Iluro and/or Baetulo are proposed as the ports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…4B). Precipitation of secondary calcite in amphorae from shipwreck has also been reported in previous studies (Buxeda I Garrigós et al 2005;Martínez Ferreras et al 2015), and in pottery buried in terrestrial sites (Freestone et al 1985;Buxeda I Garrigós and Cau Ontiveros 1995;Buxeda I Garrigós 1999;Maritan and Mazzoli 2004;Belfiore et al 2007;Maritan 2020). In our study, both processes were recognised in the calcareous matrix of Fabric 1, and this may have been due to the redistribution of carbonate material from the clay matrix and/or microfossil inclusions, as Cau noted.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…4B). Precipitation of secondary calcite in amphorae from shipwreck has also been reported in previous studies (Buxeda I Garrigós et al 2005;Martínez Ferreras et al 2015), and in pottery buried in terrestrial sites (Freestone et al 1985;Buxeda I Garrigós and Cau Ontiveros 1995;Buxeda I Garrigós 1999;Maritan and Mazzoli 2004;Belfiore et al 2007;Maritan 2020). In our study, both processes were recognised in the calcareous matrix of Fabric 1, and this may have been due to the redistribution of carbonate material from the clay matrix and/or microfossil inclusions, as Cau noted.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies of amphorae from shipwrecks have identified the same elements with great potential for alteration in the marine environment (Nieto and Picon 1986;Taylor et al 1997;Martínez Ferreras et al 2015). The alkaline elements, such as Cs, K and Rb, are depleted in amphorae from the marine environment (Maritan 2020), as in our Fabrics 1 and 3.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations